Electrospinning a Dye-Sensitized Solar Cell - Kohn, Sophia; Wehlage, Daria; Juhász Junger, Irén; Ehrmann, Andrea (Catalysts)
Dye-sensitized solar cells (DSSCs) offer new possibilities to harvest solar energy by using non-toxic inexpensive materials. Since they can generally be produced on flexible substrates, several research groups investigated possibilities to integrate DSSCs in textile fabrics, either by coating full fabrics with the DSSC layer structure or by producing fiber-shaped DSSCs which were afterwards integrated into a textile fabric. Here we show a new approach, electrospinning all solid layers of the DSSC. We report on electrospinning the counter electrode with a graphite catalyst followed by a thin nonconductive barrier layer and preparing the front electrode by electrospinning semiconducting TiO2 from a polymer solution dyed with natural dyes. Both electrodes were coated with a conductive polymer before the system was finally filled with a fluid electrolyte. While the efficiency is lower than for glass-based cells, possible problems such as short-circuits—which often occur in fiber-based DSSCs—did not occur in this proof-of-concept. Since graphite particles did not fully cover the counter electrode in this first study, and the typical bathochromic shift indicating adsorption of dye molecules on the TiO2 layer was not observed, several ways are open to increase the efficiency in forthcoming studies.